Customer experience innovation : how to get a lasting market edge - Dew, Robert; Allen, Cyrus (Emerald Publishing Limited, 2018)
This book outlines innovative processes used to research, conceive and develop innovations in the Customer eXperience (CX) space for both large and small companies.